The Anaysis Study of Comparison of Effectiveness, Efficacy and Safety of Different Technique for Treating Jaw Fractures: A Comprehensive Systematic Review - Chindy Septia Ningsih; Achmad Firdi Tanzil (International Medical Journal Corp. Ltd, 2025)
Background: Maxillofacial trauma often results in mandibular fractures, requiring effective and safe management techniques. Techniques like Erich arch bars, intermaxillary fixation (IMF) screws, and miniplate configurations have evolved to improve outcomes. Evidence-based practice is crucial in selecting appropriate techniques for treating jaw fractures, considering factors like functional outcomes and complication rates. Methods: This systematic review followed PRISMA 2020 guidelines, concentrating solely on full-text articles published in English from 2015 to 2025. Editorials and review articles lacking a DOI were excluded to maintain the quality of sources utilized. A literature review was performed using reputable databases such as ScienceDirect, PubMed, and SagePub to identify pertinent studies. Result: The initial database search turned up over 90 relevant publications on the subject. Following a three-stage screening process, eight papers satisfied the predefined inclusion criteria and were chosen for further analysis. Each study underwent a rigorous critical evaluation, allowing for a complete examination of the effectiveness, efficacy, and safety of different techniques for treating jaw fractures. This systematic methodology guaranteed that the analysis was founded on high-quality evidence, well matched with the study's objectives, and capable of giving valuable insights into this complex association. Conclusion: Techniques for managing mandibular fractures are crucial for improving patient outcomes. IMF screws, Erich arch bars, and 3D mini plates offer advantages in comfort and efficiency. A tailored approach, including locking miniplate systems and embrasure wires, is essential for achieving better outcomes. Evidence-based decision-making is essential for future advancements in maxillofacial trauma care.